Sedimentologi Batugamping Formasi Jayapura di Sepanjang Lintasan Dewarebru, Mamei-Waibron, Jayapura - Sigit Maryanto; Dian Hari Saputra; Sonia Rijani; M Luthfi Faturrakhman (Jurnal Geologi dan Sumberdaya Mineral, 2020)
The Pleistocene of the Jayapura Formation limestones well cropped out at Dewarebru Section, Mamey-Waybron, Jayapura Regency. Detailed descriptions of rock outcrops and petrography analysis of selected limestone samples is used to find out the limestone sedimentology characters. This Jayapura limestone was divided onto four limestone facies, including lithoclastic rudstone, bioclastic packstone, bioclastic grainstone and bioclastic wackesone rock facies. The rocks was deposited in a fore slope talus forming submarine alluvial fan, furthermore the rocks was deposited in a local slope on the back reef environment.Keywords: Limestone, petrography, stratigraphy, sedimentology, Jayapura